Primary healthcare professionals' attitudes toward patients with current or previous drug use - Lars Garpenhag; Disa Dahlman (Taylor & Francis Group, 2024)
Objective People with current or previous drug use (PCPDU) often lack long-term healthcare contacts in primary healthcare (PHC). While international research has shown negative attitudes toward PCPDU in healthcare, PHC professionals' attitudes toward PCPDU have not been assessed in Sweden. The aim of this study was to investigate PHC professionals' attitudes to PCPDU, and to compare attitudes toward people who actively use illicit drugs with those toward patients in opioid assisted treatment (OAT).Design In this survey study, respondents were asked for background data, and their attitudes toward patients using illicit drugs, OAT patients and patients with depression were assessed by using an adapted version of the Medical Condition Regard Scale (MCRS).Setting and subjects Nurses and physicians at primary healthcare centers (PHCCs) in Skåne, Sweden.Main outcome measures Mean MCRS scores, dichotomized responses to MCRS items, and associations between MCRS score and background covariates (age, sex, profession and duration of professional experience).Results Eighty-nine PHC professionals from 13 PHCCs responded (approximately 39% of relevant workforce). The median MCRS score was 44 for patients with illicit drug use and patients in OAT, and 51 for patients with depression. Drug use and OAT displayed similar minimum, maximum and interquartile range values as well, while scores regarding depression displayed a higher minimum value and smaller spread. No significant associations were found between background covariates and MCRS scores for either drug use or OAT.Conclusions The results indicate widespread negative attitudes to PCPDU, with implications for health equity in the clinic. Further studies are needed to see if the results reflect attitudes in Swedish PHC in general.Key PointsPeople with current or previous drug use (PCPDU) often lack necessary primary healthcare (PHC) and are commonly subject to prejudice.Swedish PHC professionals held more negative attitudes toward PCPDU than toward patients with depression.Attitudes toward patients with active drug use and patients in opioid assisted treatment (OAT) were almost identical.Study findings have potential implications for the health of PCPDU as well as health equity in the clinic.Widespread negative attitudes to PCPDU in our sample indicate the need of larger-scale studies of attitudes toward PCPDU in Swedish PHC.